Responsabilidade social corporativa e o sucesso competitivo das empresas agroexportadoras da província de Barranca - Valverde Mendoza, Magna Teodomiro (2022)
This research aims to analyze the influence of corporate social responsibility on the competitive success of agro-export companies in the province of Barranca. Corporate social responsibility (CSR) is the key exercise of the historical evolution of the entities that dates back a cycle, from the very concept a continuous renewal is proposed that has been enabling its positioning. A descriptive, correlational and non-experimental methodology was used, for the collection of information a questionnaire was elaborated, which was constituted by 15 agro-export companies from the province of Barranca and the questionnaire survey system was applied through the simple random sampling system.